Wajah Multikultural Pesantren dalam Bingkai Ke-Indonesiaan - Muhammad Rais Akbar , Rais; Imam Bashori, Imam (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2020)
Pesantren since its inception until now becomes one of the most center of Islamic studies trusted by Moslem. Religious education activities in Pesantren are considered comprehensive because not only transfer of konwoledge, but also transfer of value; not only based on understanding theory, but also the practice of worship at all once; not only rely on a memorized of scientific theories but also familiarize themselves in ritual traditions; Not only rhetorical promote the concept, tawassuth, and tawazun, but also implement in the practice level of pesantren’s life. This research is a library research. Where, the library’s data found is studied using descriptive analysis. The result of this study is pesantren has double power, it means are kyai as he leader of pesantren and pesantren itself as an institution and education system. This dual power is capable Moderate cadres, persevere, always trying, discipline and give priority to society importance.